Lower urinary tract symptoms associated with prostatitis - Nickel, J. Curtis (Canadian Medical Association, 2012)
Approximately 50% to 60% of men with chronic prostatitis experience troublesome lower urinary tract symptoms (LUTS). Individual interventions yield statistically significant but minimally important improvements in clinical trials. Research has shown that categorizing patients with prostatitis by phenotype is an effective way to rationally select therapy and maximize the impact on symptom reduction and improve quality of life.